2017
DOI: 10.1007/s10792-017-0610-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with multiple recurrences of nonspecific orbital inflammation aka orbital pseudotumor

Abstract: Younger patients and those with bilateral disease are more apt to have recurrences of NSOI. Other factors that increase the risk of multiple recurrences include a T-sign, optic disc edema, poor initial response to steroids, a sclerosing variant, a recurrence within 3 months, and those who underwent a rapid steroid taper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The precise pathophysiological basis of NSOI remains uncertain. Some studies have suggested associations with Streptococcal pharyngitis, viral upper respiratory infection, or other autoimmune conditions such as rheumatologic disease, multifocal fibrosis, and Crohn's disease [ 3 , 4 ]. NSOI manifests a spectrum of clinical presentations, ranging from lacrimal gland inflammation, known as dacryoadenitis, to myositis affecting one or several extraocular muscles, alongside a cadre of other less typical symptoms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The precise pathophysiological basis of NSOI remains uncertain. Some studies have suggested associations with Streptococcal pharyngitis, viral upper respiratory infection, or other autoimmune conditions such as rheumatologic disease, multifocal fibrosis, and Crohn's disease [ 3 , 4 ]. NSOI manifests a spectrum of clinical presentations, ranging from lacrimal gland inflammation, known as dacryoadenitis, to myositis affecting one or several extraocular muscles, alongside a cadre of other less typical symptoms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Most of the patients have monophasic disease course, but some of the patients can show recurrence. [16] In a study performed in 153 non-specific orbital inflammation with a single or multiple recurrences showed that younger age, bilateral disease, partial initial steroid response increased risk of recurrence. [16] Additionally, there may be some risk factors precipitating the disease recurrence in the presence of infection [17,18] and autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…[16] In a study performed in 153 non-specific orbital inflammation with a single or multiple recurrences showed that younger age, bilateral disease, partial initial steroid response increased risk of recurrence. [16] Additionally, there may be some risk factors precipitating the disease recurrence in the presence of infection [17,18] and autoimmune disease. [19,20] Also, obesity, pregnancy, and bisphosphonate use may also cause disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological roots of NSOI remain shrouded in uncertainty. However, recent investigations hint at its potential linkage with a constellation of factors, including Streptococcal pharyngitis, viral upper respiratory infections, and a gamut of autoimmune phenomena such as rheumatologic conditions, multifocal fibrosis, and Crohn’s disease ( 2 , 3 ). Manifestations of NSOI are heterogenous, ranging from lacrimal gland inflammation and extraocular muscle myositis to other less common presentations ( 4 ).…”
Section: Introductionmentioning
confidence: 99%